Genetic Analysis of Floral Symmetry Transition in African Violet Suggests the Involvement of Trans-acting Factor for CYCLOIDEA Expression Shifts - Hsu, Hui-Ju; He, Cheng-Wen; Kuo, Wen-Hsi; Hsin, Kuan-Ting; Lu, Jing-Yi; Pan, Zhao-Jun; Wang, Chun-Neng (Frontiers in Plant Science, 2018)
With growing demand for ornamental use, African violet (Saintpaulia ionantha) has been popular for variations in colors, shapes and their rapid responses to artificial selection. Wild type African violet (WT) is characterized by flowers with bilateral symmetry yet reversals to showy radially symmetrical flowers such as dorsalized (DA) and ventralized actinomorphic (VA) peloria are common. Genetic crosses among WT, DA and VA revealed that these floral symmetry transitions are likely to be controlled by three alleles at single locus in which the levels of dominance are in a hierarchical fashion. To investigate whether floral symmetry gene was responsible for these reversals, orthologues of CYCLOIDEA (CYC) were isolated and correlated their expressions to floral symmetry transitions. Quantitative RT-PCR and in-situ results indicated dorsal specific CYCs expression in WT S. ionantha (SiCYC1A and SiCYC1B) were shifted in DA with extended expression heterotopically to all petals, but in VA, SiCYC1s’ dorsally specific expressions were greatly reduced. Selection signature analysis revealed that the major high-expressed copy of SiCYC1A had been constrained under purifying selection, while the low expressed helper SiCYC1B, appeared to be relaxed from purifying selection after the duplication into SiCYC1A and SiCYC1B. Heterologous expression of SiCYC1A in Arabidopsis showed petal growth retardation which was attributed to limited cell proliferation. While expression shifts of SiCYC1A and SiCYC1B correlate perfectly to the resulting symmetry phenotype transitions in F1s of WT and DA, there is no certain allelic combination of inherited SiCYC1s associated with specific symmetry phenotypes. This indicates that although the expression shifts of SiCYC1A/1B are responsible for the two contrasting actinomorphic reversals in African violet, they are likely controlled by upstream trans-acting factors or epigenetic regulations.